Dampak Pelaksanaan Kebijakan “Kemenag Sultra Bersahabat” terhadap Penciptaan Kondisi Damai - Rahmad (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
The Regional Office of the Ministry of Religious Affairs of Southeast Sulawesi Province initiated a quite brilliant movement, namely the “Friendly Southeast Sulawesi Ministry of Religious Affairs Movement”, an initiative from the Regional Office of the Ministry of Religious Affairs of Southeast Sulawesi Province to strengthen and accelerate the implementation of a culture of life that is Clean, Religious, Polite, Harmonious based on Technology. The concept of the